Acute surgical abdomen - Borda-Luque, Giuliano (2025)
Acute surgical abdomen is a common presentation among patients in the emergency room, necessitating timely andaccurate diagnosis and intervention by physicians and surgeons to mitigate morbidity and mortality. This narrative reviewsynthesizes clinical guidelines, journal papers, and recent literature to provide a comprehensive overview of the most prevalentconditions contributing to acute surgical abdomen in our healthcare system, with a particular focus on diagnostic strategies anddefinitive therapeutic approaches.